General Vasiliy (Barsegh) Beibutov in the Crimean (Eastern) War - Eghiazaryan, Karine (History and Culture, 2025)
The article is devoted to highlighting the activities of the famous Armenian general Vasiliy Behbutov in the Eastern (Crimean) War, in the battles of Bash-Kadiklar and Kyruk-Dara, which were part of it. The figures of the Armenian people made a worthy contribution to the victories of the Russian army in the 19th and early 20th centuries with their fighting skills and heroic deeds, greatly contributing to the spread of the glory of the Russian armed forces.Vasili Behbutov has a unique place in the brilliant constellation of Armenian generals serving in the Russian army. Behbutov is the expression of the brave spirit of the Armenian people, the living embodiment of the fighting friendship of the Armenian and Russian peoples. As a skilled and brave military leader, he was very popular both among his contemporaries and later generations.
Keywords: Vasily (Barsegh) Behbutov; Crimean (Eastern) Wa; Caucasian Front; Abdy-Pasha; Battle of Bayandur; Bash-Kadiklar; Kyuruk-dara